1997
DOI: 10.2307/1468022
|View full text |Cite
|
Sign up to set email alerts
|

Dispersal and Recruitment in Streams: Evidence from Genetic Studies

Abstract: Analysis of genetic variation among populations of stream invertebrates provides a measure of the consequences of effective dispersal, and can be used to determine the extent of movement within and between streams and to infer the likely mechanisms involved. In our recent studies of rainforest stream invertebrates, we have found considerable genetic differentiation among populations of fully aquatic taxa, indicating limited in-stream movement on a very small scale. Adult flight appears to be the principal mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
213
4

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(233 citation statements)
references
References 37 publications
(38 reference statements)
16
213
4
Order By: Relevance
“…Stream invertebrates are generally poor fliers and can only migrate relatively short distances during their terrestrial stages. Analysis of genetic variation among stream invertebrate populations suggests that dispersal capability and reproductive strategy of adult invertebrates is a limiting factor in their ability to move across large spatial scales (Bunn and Hughes 1997).…”
Section: Biome Levelmentioning
confidence: 99%
“…Stream invertebrates are generally poor fliers and can only migrate relatively short distances during their terrestrial stages. Analysis of genetic variation among stream invertebrate populations suggests that dispersal capability and reproductive strategy of adult invertebrates is a limiting factor in their ability to move across large spatial scales (Bunn and Hughes 1997).…”
Section: Biome Levelmentioning
confidence: 99%
“…In contrast, fully lotic species are frequently genetically structured within watersheds or even within reaches (Bunn and Hughes, 1997;Marten et al, 2006). Lotic habitats are rare in the South Pacific, occurring only on volcanic islands that are tall enough to generate their own adiabatic rainfall.…”
Section: Introductionmentioning
confidence: 99%
“…The 'patchy recruitment hypothesis' (Schmidt et al 1995;Bunn and Hughes 1997) states that populations are founded by small number of females in each generation. This constitutes a bottleneck and leads to low heterozygosities.…”
Section: Heterozygositymentioning
confidence: 99%
“…Population genetics studies of mayflies (Ephemeroptera), here defined as publications that reported F selection favouring alleles at some loci in some cases, although this has not been explicitly tested for mayflies. But most of the reduction of heterozygosity in mayflies appears random, rather than at the same loci as might be expected if loci were under selection (Bunn and Hughes 1997). Parthenogenesis has been documented in a number of mayfly species (e.g.…”
Section: Heterozygositymentioning
confidence: 99%